The Compression of the Heliospheric Magnetic Structure by Interplanetary Shocks: Is the Structure at 1AU a Manifestation of Solar-Wind Turbulence or Is It Fossil Structure From the Sun? - Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2020)
As a test of the action of MHD turbulence in the solar wind, the compression of the heliospheric magnetic structure at 1AU by 109 interplanetary shocks is examined. In the magnetic structure the orientations of solar-wind strong current sheets are statistically examined versus time in the downstream plasmas after shock compression. If the current sheets of the solar wind are features of an active MHD turbulence, they should be destroyed and remade with isotropic orientations on the timescale of an eddy-turnover time. If the current-sheet orientations remain anisotropic after the shock compression, it is an indication that the current sheets of the solar wind are not created by MHD turbulence. This statistical analysis finds no evolution of the current-sheet orientations after the solar wind is compressed by the shocks, implying a non-turbulent origin of the current sheets. A possibility is that the heliospheric magnetic structure at 1 AU is fossil structure from the solar corona.